Utilization of bidara arab leaf extract (Ziziphus mauritiana Lam.) as an antibacterial agent and Its application in herbal liquid soap formulation - Yola Desnera Putri; Septiya Hasanah; Sohadi Warya; Adit Andriyannto (Journal of Midwifery and Nursing, 2026)
Bidara arab leaves (Ziziphus mauritiana Lam.) are known to contain bioactive compounds such as flavonoids, tannins, and alkaloids, which contribute to their antibacterial activity. These secondary metabolites make bidara arab leaves a promising natural source for antibacterial agents. In this study, the ethanol extract of bidara arab leaves was utilized and applied in the formulation of herbal liquid soap. The extraction process was carried out using the maceration method with 70% ethanol as the solvent. The extract was then evaluated for its Minimum Inhibitory Concentration (MIC) using the agar diffusion method against Staphylococcus aureus and Escherichia coli. Furthermore, the extract was incorporated into a liquid soap formulation prepared using the hot process method. The evaluation of the formulation included organoleptic properties, pH, specific gravity, free alkali, total fatty acid, microbial contamination, viscosity, and foam stability according to SNI 06-4085-1996.The results showed that the extract yield was 12.59% with an MIC value of 5.5%, which inhibited the growth of Staphylococcus aureus but not Escherichia coli. The formulated liquid soap met most quality parameters, except for pH and free alkali. Additionally, antibacterial testing showed an inhibition zone of 10.59 mm, indicating that the formulation exhibited effective antibacterial activity.